South Pole Ice Core Isotopes of N2 and Ar - Morgan, Jacob; Severinghaus, Jeffrey P. (IEDA: US Antarctic Program Data Center, 2022)
We present measurements gas measurements from the South Pole Ice Core, including the isotopic composition of molecular nitrogen (δ15N) and argon (δ40Ar), and the argon-nitrogen ratio (δAr/N2). The measurements were made between approximately 490 and 1310 m depth, which is between 5 and 30 kyr BP on the SP19 Gas Chronology. The measurements allow us to reconstruct the past amounts of gravitational and thermal fractionation in the firn and thus reconstruct past firn thickness and temperature gradient. These reconstructions are also included.